A multisite randomized controlled trial of Seeking Safety vs. Relapse Prevention Training for women with co-occurring posttraumatic stress disorder and substance use disorders. Issue 1 (31st December 2019) - Schäfer, Ingo; Lotzin, Annett; Hiller, Philipp; Sehner, Susanne; Driessen, Martin; Hillemacher, Thomas; Schäfer, Martin; Scherbaum, Norbert; Schneider, Barbara; Grundmann, Johanna
ABSTRACT: Background : Co-occurring posttraumatic stress disorder (PTSD) and substance use disorders (SUD) are associated with a more severe course and worse outcome than either disorder alone. In Europe, few treatments have been evaluated for PTSD and SUD. Seeking Safety, a manualized, integrated, cognitive-behavioural treatment, has been shown to be effective in studies in the USA. Objective : To test the efficacy of Seeking Safety plus treatment as usual (TAU) in female outpatients with PTSD and SUD compared to Relapse Prevention Training (RPT) plus TAU and TAU alone. Method : In five German study centres a total of N =  343 women were randomized into one of the three study conditions. PTSD severity (primary outcome), substance use, depression and emotion dysregulation (secondary outcomes) were assessed at baseline, post-treatment, as well as at three months and six months post-treatment. Results : Treatment participants attended M =  6.6 sessions (Seeking Safety) and M =  6.1 sessions (RPT). In an intent-to-treat analysis, Seeking Safety plus TAU, RPT plus TAU and TAU alone showed comparable decreases in PTSD severity over the course of the study. Seeking Safety plus TAU showed superior efficacy to TAU alone on depression and emotion regulation and RPT plus TAU was more effective than TAU alone on number of substance-free days and alcohol severity. Minimum-dose analyses suggest additional effects of both programmes among participants who attended at least eight group sessions. Conclusions : With respect to PTSD symptoms, a brief dose of Seeking Safety and RPT in addition to TAU was not superior to TAU alone in women with PTSD and SUD. However, Seeking Safety and RPT showed greater reductions than TAU alone in other domains of psychopathology and substance use outcomes respectively. Future studies should investigate further variables, such as what aspects of each treatment appeal to particular patients and how best to disseminate them.